Thermomechanical properties of poly(lactic acid) films reinforced with hydroxyapatite and regenerated cellulose microfibers. Issue 20 (15th May 2014) - Mahboubi Soufiani, Arman; Salehi, Masoud; Skrifvars, Mikael; Persson, Maria; Cho, Sung‐Woo
ABSTRACT Novel composite films constituted of poly(lactic acid) (PLA), hydroxyapatite (HAp), and two types of regenerated cellulose fillers—particulate and fibrous type—were produced by melt extrusion in a twin‐screw micro‐compounder. The effect of the film composition on the tensile and dynamic mechanical behavior and the HAp dispersion in the PLA matrix were investigated thoroughly. Appearance of crazed regions and prevention of HAp aggregation in the PLA matrix were elucidated in the composites with up to 15 wt % particulate cellulose content, which was the main reason for only slight reduction in the tensile properties, and consequently trivial degradation of their pre‐failure energy absorption as compared to neat PLA films. Superior dynamical energy storage capacities were obtained for the particulate cellulose modified composites, while their fibrous counterparts had not as good properties. Additionally, the anisotropic mechanical behavior obtained for the extruded composites should be favorable for use as biomaterials aimed at bone tissue engineering applications. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40911.